2016
DOI: 10.5603/kp.a2015.0143
|View full text |Cite
|
Sign up to set email alerts
|

The value of the Duke treadmill score in predicting the presence and severity of coronary artery disease

Abstract: A b s t r a c t Background and aim:We aimed to investigate the role of the Duke treadmill score (DTS) in predicting the presence and severity of coronary artery disease (CAD) by using the SYNTAX score (SS), and also to determine the cut-off value of DTS for both the presence and severity of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
8
2
Order By: Relevance
“…but the DTS was not a predictor of a high SYNTAX score according to the multivariate logistic regression analysis. There are several differences between our and the study of Günaydın et al [23] which may explain the discrepancy in results. For example, in contrast to Günaydın study, our study population was larger (406 vs. 267 patients in Günaydın study), we included patients at higher cardiovascular risk, such as those with PAD and chronic renal failure, and we excluded patients with normal coronary arteries and noncritical stenosis (≤50%).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…but the DTS was not a predictor of a high SYNTAX score according to the multivariate logistic regression analysis. There are several differences between our and the study of Günaydın et al [23] which may explain the discrepancy in results. For example, in contrast to Günaydın study, our study population was larger (406 vs. 267 patients in Günaydın study), we included patients at higher cardiovascular risk, such as those with PAD and chronic renal failure, and we excluded patients with normal coronary arteries and noncritical stenosis (≤50%).…”
Section: Discussioncontrasting
confidence: 95%
“…On the other hand, in a cohort of 258 patients with EST and coronary angiography, Dzenkeviciute et al [22] demonstrated a weak correlation (r = -0.173; p = 0.007) between the two scores. Günaydın et al [23] reported that the DTS was an independent predictor of a high SYNTAX score in 267 patients who underwent coronary angiography after a positive EST [23]. In our study, patients with a high SYNTAX score had a more negative DTS, FIGURE 1.…”
Section: Discussionsupporting
confidence: 50%
“…Calculation of diagnostic values is done based on Chisquared table and obtained a sensitivity of 90%, specificity of 61%, negative predictive value of 91.6%, and positive predictive value of 60%. The results of this study have better sensitivity and specificity than studies conducted by Gunaydin et al 9 who assessed the DTS relationship with the severity of coronary artery disease assessed by Syntax and obtained AUC of 0.83 (IK 0.7-0.88) with sensitivity of 74 % and specificity of 73%. 4 The diagnostic value of DTS sensitivity obtained in this study is also better than the diagnostic value based on study conducted by Tamargo et al 15 , where high risk DTS (DTS <-11) has a sensitivity of 30.8%, specificity of 90.5%, for detecting coronary lesions severity.…”
Section: Discussioncontrasting
confidence: 53%
“…7 Duke Treadmill Score (DTS) has been shown to have a strong correlation with the complexity of coronary artery lesions assessed by Syntax. 8,9 However, DTS does not describe the role of risk factors for coronary heart disease in the complexity of coronary artery lesions, there is no data regarding the addition of risk factors for CHD in DTS diagnostic values in predicting the complexity of coronary artery lesions assessed based on Syntax.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies in this field, and the diagnostic and prognostic value of DTS is quite well defined [2][3][4][5][6][7][8][9]. However, a possible limitation of earlier studies is that the results were obtained before the use of current medical therapies that significantly improve patient outcomes, such as statin therapy to appropriate low-density lipoprotein cholesterol (LDL-C) goals and perhaps lower blood pressure (BP) goals [10].…”
Section: Introductionmentioning
confidence: 99%